CREDIT SUPPLY SHOCKS AND ECONOMIC ACTIVITY IN BRAZIL - Costa Filho, Adonias Evaristo da (Análise Econômica, 2019)
This paper studies the role of credit supply shocks in Brazil, through Bayesian Vector Autoregressions (BVARs) with sign restrictions. It is found that credit supply shocks, either standalone or associated with the bank lending channel of monetary policy, lead to relatively mild eects on output growth. Despite the credit deepening observed in the last decade, credit shocks were not prominent drivers of business cycles in Brazil.